PENGARUH PROGRAM ANTI KEMISKINAN DAN PENINGKATAN PENDAPATAN PETANI (STUDI KASUS DI KELOMPOK TANI KARYA MAKMUR KABUPATEN PACITAN) - Danny Bastian (Journal of Indonesian Applied Economics, 2009)
This research is aimed at analyzing: (1)  farmer’s perception towards initiating AntiPoverty Program-APP  (2) the difference in farmers’ income before and after accept-ing the Program (3) Internal and external influencing factors to achieve the program’sgoal. It was found that (1) farmers had positive response towards the Program. Mostfarmers agreed that the program had increased their production even though somestill said no. (2) There was an increase in farmers’ income as large as 21.03% growthafter experiencing  in APP.  (3) Strategy adopted significantly  influenced the way  itreached the goal. Aggressive strategy was applied by utilizing all strengthening fac-tors internally and externally. It was recommended that the Karya Makmur farmergroup  in Pacitan Region ought to  improve  farmers self–reliance through guidanceand counseling,  to develop partnership  in agro  industrial activities  for  increasingproduction and income, to utilize the advantage of soft-loan.Keywords: farmer’s perception, Anti Poverty Program, self–reliance, partnership,soft-loan